2009
DOI: 10.1038/nri2451
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing invariant NKT cells in vaccination strategies

Abstract: To optimize vaccination strategies, it is important to use protocols that can 'jump-start' immune responses by harnessing cells of the innate immune system to assist the expansion of antigen-specific B and T cells. In this Review, we discuss the evidence indicating that invariant natural killer T (iNKT) cells can positively modulate dendritic cells and B cells, and that their pharmacological activation in the presence of antigenic proteins can enhance antigen-specific B- and T-cell responses. In addition, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
334
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 323 publications
(339 citation statements)
references
References 121 publications
2
334
2
1
Order By: Relevance
“…Even more, other unconventional T cell subsets may drive similar reactions, albeit in response to different stimuli and in different anatomical contexts, arguing for a general role of innate T cell subsets as natural adjuvants to promote protective immune responses. In analogy to the exploitation of iNKT cells in the clinic [193][194][195]223,224], approaches specifically targeting Vc9/Vd2 T cells may have a similar potential as vaccine adjuvant, to boost immune responses against pathogens and tumors and to modulate autoimmune responses.…”
Section: Innate Regulation Of Adaptive Immune Responses: Vd2 + Versusmentioning
confidence: 99%
“…Even more, other unconventional T cell subsets may drive similar reactions, albeit in response to different stimuli and in different anatomical contexts, arguing for a general role of innate T cell subsets as natural adjuvants to promote protective immune responses. In analogy to the exploitation of iNKT cells in the clinic [193][194][195]223,224], approaches specifically targeting Vc9/Vd2 T cells may have a similar potential as vaccine adjuvant, to boost immune responses against pathogens and tumors and to modulate autoimmune responses.…”
Section: Innate Regulation Of Adaptive Immune Responses: Vd2 + Versusmentioning
confidence: 99%
“…In contrast to other MHC classes, CD1d is essentially monomorphic and can bind to a large selection of self, non-self and synthetic antigens [25]. Both human and murine intestinal epithelial cells (IEC) express CD1d [26], and therefore are capable of activating iNKT cells in the intraepithelial and lamina propria (LP) compartments [27]. CD1d is also expressed on intestinal APCs and B cells.…”
Section: Inkt Cellsmentioning
confidence: 99%
“…More recently Lee et al [46] characterized circulating MAIT cells in a large sample of 133 healthy adults and reported high variability in circulating MAIT cell numbers across subjects (0.19-21.7%). Although no significant differences in numbers between males and females were found there was a significant decrease in MAIT cell numbers in elderly subjects (n = 45, ages 61-92) versus young subjects (n = 44, ages [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Characteristics Of Mait Cellsmentioning
confidence: 99%
“…71 Similarly, other glycospingolipids, such as a-GalCer, have been shown to alter the DC-NKT cell cross talk or to affect other regulatory T cells (Tregs). 133,134 GC promotes regulatory T cells Recent studies have suggested that glycosphingolipids can promote Tregs. This effect can be mediated by DCs or by cross talk between NKT cells and Tregs.…”
Section: Gc As a Ligand For DC Cellsmentioning
confidence: 99%